A Comparison of Palm Oil, Beef Tallow, and Corn Oil Effect on Serum Glucose and Lipid Profile in Rats Fed a High-Fat Diet - Utama, Zaki; Ningrum, Andriati; Mayangsari, Yunika; Raharjo, Sri (agriTECH, 2024)
This research aimed to investigate the influence of three types of palm oil products (RBDPO (refined bleached deodorized palm oi), RPO (red palm oil), and PKO (palm kernel oil)), on serum glucose and lipid profile of Sprague Dawley rats fed with experimental diet containing 20% of oils, comparing these effects with those of with animal- base oil (beef tallow) including corn oil as a representative from vegetable oil. The diet with level of fat 20% given to two groups (with and without AOM (azoxymethane)) of male Sprague Dawley rats for 13 weeks. The results exhibit that corn oil caused the lowest value of serum glucose (p < 0.05) in both AOM and non-AOM groups. Compared to other groups, beef tallow diet significantly increased serum triglycerides, cholesterol, and LDL, followed by RPO/PKO, RBDPO, and corn oil, respectively (p < 0.05). Meanwhile, corn oil diet produced the highest level of serum HDL, followed by RBDPO, PKO/RPO, and beef tallow (p < 0.05).